Natural Course of Neonatal Progeroid Syndrome - Jia-Woei Hou (Pediatrics and Neonatology)
Several progeroid disorders presenting a specific “old-man” appearance since birth or childhood have been described. Here, five patients with a history of severe intrauterine and postnatal growth retardation and pseudohydrocephaloid cranium noted after birth that were suggestive of neonatal progeroid syndrome (NPS) or Wiedemann-Rautenstrauch syndrome are reported. We discuss the natural course of the syndrome. Methods: A series of anthropometric measurements, imaging, dual energy X-ray absorptiometry, and endocrine investigations to assess metabolic complications such as hyperinsulinemia and dyslipidemia were performed on these five patients who were followed for 1-7 years. Screening of inborn errors, karyotyping, chromosomal breakage rates and DNA mutational studies with direct sequencing of LMNA, ERCC8 and ZMPSTE24 genes were also performed. Results: Generalized lipodystrophy was noted in all patients except for regions such as the cheeks, hands and feet. All cases had failure to thrive, microcephaly, ear dysplasia, laryngomalacia, hearing impairment, gastro-esophageal reflux disease, constipation, abnormal dentition, dermatitis/acrodermatitis enteropathica, hyperpigmentation of the skin, very low insulin-like growth factor I levels with delayed bone age, relative hypolipidemia, initial camptodactyly/joint contracture, progressive kyphoscoliosis, osteoporosis with loose joints, ventriculomegaly, and generalized organic aciduria. Other findings included inguinal hernia, hypothyroidism or persistent hyperthyrotropinemia, cryptorchidism, hip dysplasia, growth hormone deficiency, cloudy cornea with congenital glaucoma, neonatal teeth, cardiac defects, basal ganglia calcification and seizure disorder. These patients with NPS did not show hyperinsulinemia or dyslipidemia. Their karyotypes were all normal, while the chromosomal breakage test showed markedly increased breakage rates in four patients. LMNA, ERCC8, or ZMPSTE24 gene mutations could not account for the disorders in these patients. Four patients died after sepsis or aspiration pneumonia at the age of 1.1, 4, 6.2 and 7.5 years. Conclusion: Increased chromosomal breakage and the presence of basal ganglia calcification after early childhood suggest that DNA repair defects are involved in the pathogenesis of this disorder. This rare disorder represents a complex of symptoms with unknown cause and pathogenesis, and more than one disease may account for the clinical variability of NPS.